Activity patterns of primary school children during participation in The Daily Mile - Lorna M. Hatch (Nature Portfolio, 2021)
Abstract The Daily Mile is a popular physical activity initiative in primary schools, yet little is known regarding the activity patterns of children during The Daily Mile. Eighty children (10.4 ± 0.7 years) participated in The Daily Mile (20-min). Activity patterns were assessed using global positioning systems (total distance and age-specific speed zones), alongside heart rate. Cardiorespiratory fitness was assessed using the Multi-Stage Fitness Test. Participants covered a distance of 2511 ± 550 m during The Daily Mile, and heart rate was 163 ± 27 beats.min−1. Participants travelled the furthest distance, and were most intermittent, during the first 5 min (main effect of time, both p < 0.001). Boys ran further and their activity was more intermittent compared to girls (main effect of sex, both p < 0.001). Moreover, the highest fit children ran further than less fit children (main effect of fitness, p < 0.001). This study provides novel evidence of the nature of physical activity during The Daily Mile; demonstrating that children covered, on average, 1.5-miles and exercised at a moderate-to-vigorous intensity. Furthermore, boys covered a greater distance and were more intermittent than girls; whilst higher fit children ran further than lower fit children. In summary, The Daily Mile makes a valuable contribution to in-school physical activity targets in all children.